2020
DOI: 10.1007/s12020-020-02465-4
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is a risk factor for prolonged SARS-CoV-2 viral shedding in lower respiratory tract samples of critically ill patients

Abstract: Purpose The length of time a critically ill coronavirus disease 2019 (COVID-19) patient remains infectious and should therefore be isolated remains unknown. This prospective study was undertaken in critically ill patients to evaluate the reliability of single negative real-time polymerase chain reaction (RT-PCR) in lower tracheal aspirates (LTA) in predicting a second negative test and to analyze clinical factors potentially influencing the viral shedding. Methods From April 9, 2020 onwards, intubated COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 18 publications
(25 reference statements)
2
28
2
Order By: Relevance
“…The recently published letter by Cano et al suggested that patients with diabetes mellitus (DM) did not show prolonged RNA viral shedding based on nasopharyngeal sampling [2]. At first glance, these data seem to be in contrast to our study showing a prolonged viral shedding in lower respiratory tract of critically ill patients [1]. However, we respectfully would underline that this discrepancy could depend on differences in demographic feature and methodological/ statistical approaches.…”
Section: To the Editorcontrasting
confidence: 99%
See 3 more Smart Citations
“…The recently published letter by Cano et al suggested that patients with diabetes mellitus (DM) did not show prolonged RNA viral shedding based on nasopharyngeal sampling [2]. At first glance, these data seem to be in contrast to our study showing a prolonged viral shedding in lower respiratory tract of critically ill patients [1]. However, we respectfully would underline that this discrepancy could depend on differences in demographic feature and methodological/ statistical approaches.…”
Section: To the Editorcontrasting
confidence: 99%
“…However, we respectfully would underline that this discrepancy could depend on differences in demographic feature and methodological/ statistical approaches. Then, the following two issues have to be considered when comparing our results [1] with that from Cano et al [2]:…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The primary objective was the description of viral shedding duration (i.e., time to negativity) in LRTS and was defined as the time between onset of symptoms and viral clearance process (i.e., first negative detection of viral RNA in LRT). Of note, we previously showed that the association of the first negative RT-PCR with a second negative result was very high (i.e., 97%) in LRTS [11]. Secondary objectives were (1) the analysis of RT-PCR viral load in LRTS and (2) the assessment of 6-week mortality.…”
Section: Definitions and Objectivesmentioning
confidence: 99%